TRPC3 Channel Activity and Viability of Purkinje Neurons can be Regulated by a Local Signalosome - Aslam, Naveed; Alvi, Farah (Frontiers in Molecular Biosciences, 2022)
Canonical transient receptor potential channels (TRPC3) may play a pivotal role in the development and viability of dendritic arbor in Purkinje neurons. This is a novel postsynaptic channel for glutamatergic synaptic transmission. In the cerebellum,TRPC3 appears to regulate functions relating to motor coordination in a highly specific manner. Gain of TRPC3 function is linked to significant alterations in the density and connectivity of dendritic arbor in Purkinje neurons. TRPC3 signals downstream of class I metabotropic glutamate receptors(mGluR1). Moreover, diacylglycerol (DAG) can directly bind and activate TRPC3 molecules. Here, we investigate a key question: how can the activity of the TRPC3 channel be regulated in Purkinje neurons? We also explore how mGluR1 activation, Ca2+ influx, and DAG homeostasis in Purkinje neurons can be linked to TRPC3 activity modulation.Through systems biology approach we show that TRPC3 activity can be modulated by a Purkinje cell (PC)-specific local signalosome. The assembly of this signalosome is coordinated by DAG generation after mGluR1 activation. Our results also suggest that purinergic receptor activation leads to the spatial and temporal organization of the TRPC3 signaling module and integration of its key effector molecules such as DAG, PKCγ, DGKγ, and Ca2+ into an organized local signalosome. This signaling machine can regulate the TRPC3 cycling between active, inactive, and desensitized states. Precise activity of the TRPC3 channel is essential for tightly regulating the Ca2+ entry into PCs and, thus, the balance of lipid and Ca2+ signaling in Purkinje neurons and, hence, their viability. Cell-type-specific understanding of mechanisms regulating TRPC3 channel activity could be key in identifying therapeutic targeting opportunities.